De affinitate declinationum in lingua Fennica, Esthonica et Lapponica. - Castrén, M. Alexander (Matthias Alexander), 1813-1852. (Helsingforsiae, 1839)
Thesis--Univ. of Helsinki. Mode of access: Internet.